Bioequivalent pharmacokinetics for generic and originator hepatitis C direct-acting antivirals - Hill, Andrew (J Virus Erad, 2018)
Mass production of low-cost, generic direct-acting antivirals (DAAs) will be required to achieve targets of eliminating hepatitis C (HCV) by 2030. The pharmaceutical companies Gilead and Bristol-Myers Squibb have granted voluntary licences (VLs) to generic companies to mass produce the DAAs sofosbuvir and daclatasvir at low cost. However, generic manufacturers need to demonstrate bioequivalent pharmacokinetics for their DAAs, compared to the originator versions, to fulfil World Health Organization standards for prequalification. The aim of this study was to determine whether generic forms of sofosbuvir and daclatasvir had bioequivalent pharmacokinetics to the originator versions. Generic companies were contacted for results of bioequivalence studies with sofosbuvir and daclatasvir, two of the most widely used DAAs in the developing world. Data on maximum concentration (C(max)) and area under the curve (AUC) were compiled from five generic companies. Pre-specified limits for the 90% confidence intervals were 80–125% of the originator pharmacokinetic concentrations for AUC, and 69–145% for C(max). The pharmacokinetics of generic sofosbuvir and daclatasvir were shown to be bioequivalent to the originator versions for all five generic companies. This is a crucial step towards securing prequalification of the manufacture of these drugs from these companies. WHO prequalification of bioequivalent generic DAAs could then permit their export to eligible countries for mass-treatment programmes. Mass-treatment with low-cost generic HCV DAAs is the most promising method to achieve the ambitious World Health Organization targets for HCV elimination by 2030.